1997
DOI: 10.1017/s0016756897006857
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the North Indian continental margin in the Ladakh–Zanskar Himalayas: implications for the timing of obduction of the Spontang ophiolite, India–Asia collision and deformation events in the Himalaya

Abstract: The collision of India and Asia can be defined as a process that started with the closing of the Tethyan ocean that, during Mesozoic and early Tertiary times, separated the two continental plates. Following initial contact of Indian and Asian continental crust, the Indian plate continued its northward drift into Asia, a process which continues to this day. In the Ladakh–Zanskar Himalaya the youngest marine sediments, both in the Indus suture zone and along the northern continental margin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(149 citation statements)
references
References 2 publications
3
137
0
Order By: Relevance
“…We define the final India-Asia collision as the timing of the final marine sedimentation (planktonic foraminifera zone P8; shallow benthic zone SBZ10; Green et al 2008) in the suture zone and along the north Indian plate margin (Garzanti et al 1987;Searle et al 1988Searle et al , 1997bRowley 1998;Zhu et al 2005;Green et al 2008). Ophiolite obduction southward onto the passive margin of Indian preceded India-Asia collision and most probably occurred during the Late Cretaceous-Palaeocene (Searle et al 1988(Searle et al , 1997b.…”
Section: Pre-collision Thickeningmentioning
confidence: 99%
See 1 more Smart Citation
“…We define the final India-Asia collision as the timing of the final marine sedimentation (planktonic foraminifera zone P8; shallow benthic zone SBZ10; Green et al 2008) in the suture zone and along the north Indian plate margin (Garzanti et al 1987;Searle et al 1988Searle et al , 1997bRowley 1998;Zhu et al 2005;Green et al 2008). Ophiolite obduction southward onto the passive margin of Indian preceded India-Asia collision and most probably occurred during the Late Cretaceous-Palaeocene (Searle et al 1988(Searle et al , 1997b.…”
Section: Pre-collision Thickeningmentioning
confidence: 99%
“…Kongur, Muztagh Ata) are not offset across the fault (Robinson et al 2007;Robinson 2009a,b). The southeastern end of the Karakoram Fault merges into the Indus-Yarlung Tsangpo suture zone south of Mount Kailas, where north-directed backthrusting occurs along the northern margin of the Indian plate (Searle 1996;Searle et al 1997b) and north-south extensional faulting occurs in the Purang graben (Murphy et al 2000;Murphy & Yin 2003). The Karakoram Fault forms one major strand along the Nubra Valley but in the Tangtse region the fault splays into two branches, the main strand, the Tangtse Fault strand, to the SW and the Pangong Fault strand to the NE, both of which display spectacular mylonites (Fig.…”
Section: Karakoram Faultmentioning
confidence: 99%
“…Prior to the India-Asia collision, India's northern continental periphery was a passive margin of the Tethys Ocean, with late Permian and Mesozoic shelf carbonates deposited over Pennian volcanics and Palaeozoic sediments (Searle et aI., 1997). During the Cretaceous, ophiolite slabs were obducted from the margins of the Tethys basin (Searle, 1983;Sinha, 1992;Osmaston, 1994;Searle et al, 1997) and the fore-arc basin of the Dras island arc was closed. Northward subduction of Mesozoic oceanic crust created an Andean style destructive plate margin and the emplacement of the Trans-Himalayan granite batholith (1 in Fig.…”
Section: Geological Evolution Of the North-western Himalayamentioning
confidence: 99%
“…These formations could not be traced to the east of Ladakh sector in Lhasa and southern Tibet region and remain a peculiarity of the northwestern Himalaya. However, tectonic models proposing two subduction zones in general assume two sutures along the entire south Asian boundary (Brookfield and Reynolds, 1981;Rai, 1983;Reynolds et al, 1983;Coward and Butler, 1985;Petterson and Windley, 1985;Srimal, 1986;Sharma, 1987;Treloar et al, 1989;Searle et al, 1997;Weinberg and Dunlap, 2000;Dunlap and Wysoczanski, 2002;Robertson and Collins, 2002;Dubois-Cote et al, 2005;Dupuis et al, 2005). This has resulted in various attempts of correlating older sutures present in Lhasa-Tibet block with the Shyok suture (Dunlap and Wysoczanski, 2002;Lacassin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Brookfield and Reynolds (1981), and Reynolds et al (1983) suggested that the Shyok suture closed in Miocene after the Late Cretaceous suturing along the Indus suture. However, Coward and Butler (1985), Petterson and Windley (1985), Treloar et al (1989) and Searle et al (1997) proposed that the Shyok suture is older than the Indus suture. Rai (1983) reported upper Cretaceous to Eocene marine fossils from the flysch of the Shyok suture zone.…”
Section: Introductionmentioning
confidence: 99%